2008
DOI: 10.21273/hortsci.43.1.236
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Supplements Affect Horticultural Traits of Greenhouse-produced Ornamental Sunflowers

Abstract: In greenhouse production, most floricultural crops are cultivated in soilless substrates, which often supply limited amounts of plant-available silicon (Si). The goal of this study was to determine the effects of Si supplementation on greenhouse-produced ornamental sunflower (Helianthus annuus L. ‘Ring of Fire’). Potassium silicate (KSiO3) substrate incorporation or weekly substrate drenches, sodium silicate (NaSiO3) foliar applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 15 publications
5
54
0
1
Order By: Relevance
“…The excessively high Si concentration in the drenching solution was presumably responsible for the decreases in flower yield and other morphological traits that were recorded in some species. Indeed, as reported by Kamenidou et al (2008), growth abnormalities were observed in ornamental sunflowers when concentrations of 100 and 200 mg L −1 Si were supplied as KSiO 3 through substrate drenching. Based on these results as well as on the results from another relevant study (Kamenidou et al, 2009), these authors concluded that the form and concentration of applied Si significantly impacts stem height and anthesis in ornamental sunflower and zinnia.…”
Section: Ornamentals and Flower Cropssupporting
confidence: 53%
See 2 more Smart Citations
“…The excessively high Si concentration in the drenching solution was presumably responsible for the decreases in flower yield and other morphological traits that were recorded in some species. Indeed, as reported by Kamenidou et al (2008), growth abnormalities were observed in ornamental sunflowers when concentrations of 100 and 200 mg L −1 Si were supplied as KSiO 3 through substrate drenching. Based on these results as well as on the results from another relevant study (Kamenidou et al, 2009), these authors concluded that the form and concentration of applied Si significantly impacts stem height and anthesis in ornamental sunflower and zinnia.…”
Section: Ornamentals and Flower Cropssupporting
confidence: 53%
“…As reported by Kamenidou et al (2008), application of Si through drenching at a concentration of 50 mg L −1 upgraded the quality of ornamental sunflower by increasing thickness and height of the flower stem, as well as the diameter of the flower head, compared with untreated controls. In Paeonia lactiflora, Si application through foliar sprays (500 mg L −1 of sodium silicate) increased resistance to lodging and the mechanical strength of the inflorescence stem (Zhao et al, 2013).…”
Section: Ornamentals and Flower Cropsmentioning
confidence: 52%
See 1 more Smart Citation
“…Enhancement of these growth parameters was most notable for plants that had a continuous supply of Si. Although Si has not been recognized as an essential element for plant growth, the beneficial effects of Si have been observed in a wide variety of plant species, particularly graminaceous plants such as rice and sugarcane as well as some cyperaceous plants (Kamenidou et al, 2008). Si may be involved in cell elongation and/or cell division and this may explain the larger plant height and pseudostem diameter observed in Si-treated plants.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the ability of Si to improve tolerance to abiotic stresses such as drought, salinity, freezing, heavy metal toxicity and biotic stresses such as disease and pests, especially in crops that actively accumulate the element (Epstein, 1999;Heine et al, 2006;Liang et al, 2008). In particular, several studies have shown that adequate uptake of Si may substantially increase tolerance to both abiotic and biotic stresses in rice, sugarcane, sunflower, tomato, wheat and other crops (Heine et al, 2006;Cai et al, 2008;Kamenidou et al, 2008;Liang et al, 2008). Plants with low Si accumulation are known to be more susceptible to fungal disease and insect feeding, as well as other biotic and abiotic stresses that adversely affect crop production.…”
Section: Introductionmentioning
confidence: 99%